'Mothers Have Become Monsters': Danger, Distress and Deviance in British Evangelical Depictions of Indian Motherhood, 1757–1857. (8th August 2018) - Major, Andrea
ABSTRACT: Images of maternal distress and maternal deviance were frequently invoked in order to mobilise British women in support of her 'heathen' sisters overseas. Yet these accounts were not uniform in their interpretation of Indian maternity, or its relationship to emerging Victorian ideals of motherhood. This paper explores ideas of maternal danger, distress and deviance as they appeared in evangelical and colonial discourses of the late eighteenth and early nineteenth century, revealing complex and ambivalent responses and challenging the idea that Indian woman were simply one-dimensional signifiers of victimhood within gendered constructions of the 'civilising mission'.